Unbiased Identification of Angiogenin as an Endogenous Antimicrobial Protein With Activity Against Virulent Mycobacterium tuberculosis - Noschka, Reiner; Gerbl, Fabian; Löffler, Florian; Kubis, Jan; Rodríguez, Armando A.; Mayer, Daniel; Grieshober, Mark; Holch, Armin; Raasholm, Martina; Forssmann, Wolf-Georg; Spellerberg, Barbara; Wiese, Sebastian; et al. (Frontiers in Microbiology, 2021)
Tuberculosis is a highly prevalent infectious disease with more than 1.5 million fatalities each year. Antibiotic treatment is available, but intolerable side effects and an increasing rate of drug-resistant strains of Mycobacterium tuberculosis (Mtb) may hamper successful outcomes. Antimicrobial peptides (AMPs) offer an alternative strategy for treatment of infectious diseases in which conventional antibiotic treatment fails. Human serum is a rich resource for endogenous AMPs. Therefore, we screened a library generated from hemofiltrate for activity against Mtb. Taking this unbiased approach, we identified Angiogenin as the single compound in an active fraction. The antimicrobial activity of endogenous Angiogenin against extracellular Mtb could be reproduced by synthetic Angiogenin. Using computational analysis, we identified the hypothetical active site and optimized the lytic activity by amino acid exchanges. The resulting peptide-Angie1-limited the growth of extra‐ and intracellular Mtb and the fast-growing pathogens Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae. Toward our long-term goal of evaluating Angie1 for therapeutic efficacy in vivo, we demonstrate that the peptide can be efficiently delivered into human macrophages via liposomes and is not toxic for zebrafish embryos. Taken together, we define Angiogenin as a novel endogenous AMP and derive the small, bioactive fragment Angie1, which is ready to be tested for therapeutic activity in animal models of tuberculosis and infections with fast-growing bacterial pathogens.